Learn to implement games with code - Quick, John M. (CRC Press, Taylor & Francis Group, 2017)
Learn to Implement Games with Code guides you through the development process as you put together a release-ready game. It is written in a friendly and conversational tone, which is suitable for a wide audience of aspiring game developers, such as yourself. You will gain practical, hands-on experience with implementing game components using code. Gradually, you will build a complete game that you can be proud of. After finishing this book, you will be prepared to start making games of your very own design.